An Imine‐Linked Metal–Organic Framework as a Reactive Oxygen Species Generator. (29th December 2020) - Li, Xiaomin; Wang, Junyi; Xue, Fengfeng; Wu, Yichen; Xu, Hualong; Yi, Tao; Li, Qiaowei
Abstract: A new metal–organic framework (MOF) with both coordination linkages and covalent linkages is prepared by coordinating Cu I with pyrazolate for an aldehyde‐functionalized trinuclear complex, and subsequent imine condensation with p‐phenylenediamine, a reaction typical for covalent organic framework (COF) synthesis. This MOF×COF collaboration yields FDM‐71 with honeycomb layers stacked in eclipsed fashion. After dissociating the Cu I ‐pyrazolate coordination in FDM‐71, the obtained organic components carry the information of structural defects, and thus vacancy identity (aldehyde‐based unit vacancy and amine‐based unit vacancy) and concentration are definitely resolved. Further to the redox catalytic activity inherited from the complex, FDM‐71 features effective photosensitizing activity. The two functions integrated in one well‐defined structure is demonstrated by its high efficiency in decomposing H2 O2 and consequent excitation of O2 to reactive oxygen species. Abstract : Constituting imine linkages between trinuclear Cu I ‐based complexes and diamine creates a metal–organic framework with honeycomb layers in eclipsed packing. Two kinds of structural vacancies are identified quantitatively by selective coordination dissociation. The structure could catalyze H2 O2 decomposition and consequently excite O2 to reactive oxygen species.